Assessing Higher Education in COVID-19 Era - Rahul Kumar (Brock University, 2020)
COVID-19 has changed how universities operate. The changes are in all spheres and caused by demands of social distancing rules predominantly mediated by various digital technologies. Applying Bauman's (1993) ethics of technology on newly initiated assessment practices, this article raises ethical concerns of relying on solutions solely manufactured by technology companies without professors' and students' input, various considerations of privacy, and overall ethical concerns that the use of any new technology raises. The article concludes by beseeching all stakeholders to collaborate to construct the tools for tomorrow that meet pedagogical needs without compromising Bauman's ethical concerns.